How the Replication and Transcription Complex Functions in Jumping Transcription of SARS-CoV-2 - Liang, Jianguang; Shi, Jinsong; Chen, Shunmei; Duan, Guangyou; Yang, Fan; Cheng, Zhi; Li, Xin; Ruan, Jishou; Mi, Dong; Gao, Shan (Frontiers in Genetics, 2022)
Background: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although unprecedented efforts are underway to develop therapeutic strategies against this disease, scientists have acquired only a little knowledge regarding the structures and functions of the CoV replication and transcription complex (RTC). Ascertaining all the RTC components and the arrangement of them is an indispensably step for the eventual determination of its global structure, leading to completely understanding all of its functions at the molecular level.. Results: The main results include: (1) hairpins containing the canonical and non-canonical NSP15 cleavage motifs are canonical and non-canonical transcription regulatory sequence (TRS) hairpins; (2) TRS hairpins can be used to identify recombination regions in CoV genomes; (3) RNA methylation participates in the determination of the local RNA structures in CoVs by affecting the formation of base pairing; and (4) The eventual determination of the CoV RTC global structure needs to consider METTL3 in the experimental design. Conclusions: In the present study, we proposed the theoretical arrangement of NSP12-15 and METTL3 in the global RTC structure and constructed a model to answer how the RTC functions in the jumping transcription of CoVs. As the most important finding, TRS hairpins were reported for the first time to interpret NSP15 cleavage, RNA methylation of CoVs and their association at the molecular level. Our findings enrich fundamental knowledge in the field of gene expression and its regulation, providing a crucial basis for future studies.